1992
DOI: 10.1111/j.1749-7345.1992.tb00767.x
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Water Quality Characteristics of Effluent from Hawaiian Aquaculture Facilities

Abstract: Ten water quality parameters were measured in influent and effluent water at 11 aquaculture facilities in Hawaii. The data were grouped into four categories based on the types of organisms cultured: freshwater fish, freshwater prawn, marine fish, and marine shrimp. Within each category, concentrations of most parameters were lognormally distributed and spanned one to two orders of magnitude. Geometric mean concentrations of suspended materials, total nitrogen, total phosphorus, and pigments were highest in eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(48 citation statements)
references
References 5 publications
4
42
0
2
Order By: Relevance
“…No presente trabalho, mesmo com as trocas de água no tratamento controle, a concentração de nitrito atingiu valores significativamente maiores em comparação ao tratamento com probióticos, o que indica maior eficiência do probiótico para manutenção da qualidade da água, sem a necessidade de renovações. Portanto, a utilização de probióticos na aquicultura permite melhoria nos parâmetros de qualidade de água, além de diminuir impactos econômicos e ambientais por meio da redução na quantidade de água utilizada e na geração de efluentes dos sistemas de produção (Ziemann et al, 1992;Wang et al, 2005).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…No presente trabalho, mesmo com as trocas de água no tratamento controle, a concentração de nitrito atingiu valores significativamente maiores em comparação ao tratamento com probióticos, o que indica maior eficiência do probiótico para manutenção da qualidade da água, sem a necessidade de renovações. Portanto, a utilização de probióticos na aquicultura permite melhoria nos parâmetros de qualidade de água, além de diminuir impactos econômicos e ambientais por meio da redução na quantidade de água utilizada e na geração de efluentes dos sistemas de produção (Ziemann et al, 1992;Wang et al, 2005).…”
Section: Resultsunclassified
“…O acúmulo desses compostos é um fator limitante nos sistemas de produção (Banerjee et al, 2010). Para solucionar esses problemas, é necessário realizar frequentes trocas de água dos tanques de cultivo, que resultam em descarga de resíduos que podem causar eutrofização do ambiente natural (Ziemann et al, 1992). Nos sistemas de cultivo com adição de probióticos, as trocas de água podem ser diminuídas ou até mesmo eliminadas, uma vez que os probióticos atuam na absorção e na decomposição da matéria orgânica na água e nos sedimentos, o que melhora a qualidade de água (Wang et al, 2005).…”
Section: Introductionunclassified
“…Similar results were obtained by Kimpara 26 , who found that there was no significant difference among the concentrations of total nitrogen, ammonia, nitrite and nitrate among treatments and among treatments themselves and the water supply. However, when Ziemann et al 33 analyzed the affluent water quality and the water effluent of fresh-water fish and shrimp ponds and that of seawater fish and shrimp, they discovered that effluent had a lower quality than that of the affluent in most parameters analyzed. In fact, concentrations of suspended material and pigments in the effluents of freshwater fish and shrimps were higher.…”
Section: Resultsmentioning
confidence: 99%
“…The water quality of shrimp farm effluent depends on a number of factors, including pond soil type, quality of influent water, stage of grow out season and management practices employed [58]. Water pollution is largely associated with the use and discharge of water in shrimp ponds [29].…”
Section: Assessment Of Water Qualitymentioning
confidence: 99%